The Role of Carbon Pricing Policy on ESG Performance in Asia Countries - Inten Meutia; Zulnaidi Yaacob; Hasni Yusrianti; Shelly F Kartasari (Indonesian Journal of Sustainability Accounting and Management, 2024)
This study analyses the relationship between countries’ regulatory context and Environment, Social, and Governance (ESG Performance). Little attention has been paid to how carbon pricing policy influences companies’ ESG performance. This study uses data from 2,600 companies from 11 countries in Asia, both with and without carbon policies, to test whether there is a difference in ESG scores between the two groups of countries. This study found that the ESG score in countries with carbon pricing policies is lower than the ESG in countries without carbon pricing policies. This difference proved to be significant. In the context of this research, Environment Modernization Theory has not been proven to be able to encourage corporate reporting activities and improve corporate environmental, social, and government (ESG) performance. The implications of this study highlight the need for a critical reassessment of carbon pricing policies, further research into their effectiveness, and a focus on regional differences to enhance ESG performance in Asia. This is the first research considering carbon pricing policy regulation in the study of ESG, especially in Asia.